Zonation of Soil Bearing Capacity from Cone Penetration Test Data: Case Study in Padang - Liliwarti; Silvianengsih; Mahardika, Tiara; Hartati; Stiyanto, Eri (International Journal of Advanced Science Computing and Engineering, 2025)
This study aims to map the zonation of soil bearing capacity in Padang City, covering five districts —Koto Tangah, Padang Barat, Nanggalo, Padang Timur, and Padang Selatan —comprising a total of 12 test points. The data were obtained from Cone Penetration Test (CPT) results, which were subsequently analysed to determine the ultimate bearing capacity of the soil, the safety factor of foundations against load eccentricity, and settlement at several test points. The analytical approach focused on assessing vertical bearing capacities, comparing estimated working loads with calculated ultimate bearing capacities, and determining settlement under representative design load conditions. From 12 test points distributed across the five districts, the results indicate that all locations exhibit safety factors significantly above the minimum requirement (FS > 3), suggesting that the ground has excellent capacity to sustain structural loads. In addition, the observed settlements are small, ranging from 0.8 mm to 6.4 mm, and remain well below the commonly accepted tolerance for foundation settlement (25–50 mm). These results support the notion that the subsurface layers in these areas are stable and do not pose a significant risk of foundation settlement. Therefore, the soil conditions at all test points can be categorised as safe, stable, and suitable to support the assumed design load of 100 kN, regardless of whether pile foundations or shallow foundations are used. The resulting soil bearing capacity zonation map is expected to serve as a practical reference for foundation planning, assisting engineers and planners in selecting appropriate foundation systems, and supporting sustainable infrastructure development in Padang City in a safer, more effective, and efficient manner.